2021
DOI: 10.47405/mjssh.v6i11.1136
|View full text |Cite
|
Sign up to set email alerts
|

Kesahan dan Kebolehpercayaan Instrumen Penilaian Kendiri Pembelajaran Ungkapan Algebra Tingkatan Dua

Abstract: Kesahan adalah sejauh mana instrumen mengukur apa yang hendak diukur dan kebolehpercayaan adalah keupayaan suatu kajian untuk memperoleh nilai yang serupa apabila pengukuran yang sama diulangi. Kesahan dan kebolehpercayaan instrumen amat penting bagi mempertahankan kejituan item soal selidik daripada kecacatan. Tujuan kajian ini adalah untuk menentukan kesahan dan kebolehpercayaan instrumen soal selidik penilaian kendiri pembelajaran Ungkapan Algebra Tingkatan Dua. Soal Selidik telah disahkan melalui kesahan m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Kesahan adalah jumlah instrumen yang mengukur apa yang sepatutnya diukur, sementara kebolehpercayaan adalah keupayaan kajian untuk menghasilkan hasil yang sama apabila pengukuran yang sama diulang (Baco & Ishak, 2021). Kesahan instrumen amat penting bagi mempertahankan kejituan item soal selidik daripada kecacatan.…”
Section: Sorotan Literaturunclassified
“…Kesahan adalah jumlah instrumen yang mengukur apa yang sepatutnya diukur, sementara kebolehpercayaan adalah keupayaan kajian untuk menghasilkan hasil yang sama apabila pengukuran yang sama diulang (Baco & Ishak, 2021). Kesahan instrumen amat penting bagi mempertahankan kejituan item soal selidik daripada kecacatan.…”
Section: Sorotan Literaturunclassified
“…Although the secondary school education system in Malaysia has experienced a curriculum transformation starting in 2017, the Ministry of Education Malaysia [1] found that the level of mastery of Malaysian students is still low in relation to basic topics in algebra. Algebra domain items related to Basic Arithmetic Operations involving Algebraic Expressions in in Programme for International Student Assessment (PISA) 2018 and Trends in International Mathematics and Science Study (TIMSS) 2019 were found to be unable to be answered well and weak in conceptual mastery [1][2][3]. Past studies also prove that secondary students are still faced with the problem of conceptual mastery in the Basic Arithmetic Operations involving Algebraic Expressions [4][5][6][7].…”
Section: A Student Learning Mastery Problems In Subtopic Of Basic Ari...mentioning
confidence: 99%
“…In addition, students have problems with remembering, recalling, procedural and conceptual knowledge [8]. Apart from that, Baco and Ishak [3] stated that the problem of student mastery stems from basic concepts that are not explained well at the initial stage, causing students to be unable to form a deep understanding of concepts.…”
Section: A Student Learning Mastery Problems In Subtopic Of Basic Ari...mentioning
confidence: 99%
See 2 more Smart Citations